Solve by using quadratic formula. Answer in simplest radical form 3x^2 + 6x + 2= 0

1 Answer | Add Yours

jeew-m's profile pic

Posted on

By using quadratic formular the roots of` ax^2+bx+c = 0 ` can be given as;

`x = (-b+-sqrt(b^2-4ac))/(2a)`

For our question;

`3x^2 + 6x + 2= 0`

`a = 3`

`b = 6`

`c = 2`

`x = (-6+-sqrt(6^2-4xx3xx2))/(2xx3)`

`x = (-6+sqrt12)/6 = (-3+2sqrt3)/3`

`x = (-6-sqrt12)/6= (-3-2sqrt3)/3`


So the answers are;

`x = (-3+2sqrt3)/3`

`x = (-3-2sqrt3)/3`

Sources:

We’ve answered 333,530 questions. We can answer yours, too.

Ask a question